MOTIVASI MASYARAKAT MELAKUKAN PENGALIHAN LAHAN DARI LAHAN PERTANIAN MENJADI LAHAN PENAMBANGAN EMAS DI JORONG TANJUNG PAUH KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG - Delrahmawati, Delrahmawati; Suarto, Edi; Keslan, Widya Prari (Pendidikan Geografi, 2013)
Indonesia was familiar nation called as agriculture country had larger farming area. All around of Indonesian village had high potency in the farming sector. However, the development of farming sector is not always yield the best product. The province of west Sumatra had any kinds of natural resources both on the land, sea and the air. For example to the larger forest and various mining material coal, gold, ore, sulfur and other. Jorong Tanjung Pauh was an area had high potency the golden mining. This research was conducted aim to observe and analysis data of societyâs motivation in doing the Functional Change of Area from Farming become Golden Mining at Jorong Tanjung Pauh IV Nagari District of Sijunjung Regency.Â The type of this research was qualitative study; informant of research was conducted by using snow ball sampling technique, the researcher interview the informant regularly. Techniques of collecting data were interview, observation, filed note and documentation by using photo. The data analysis of this research used data reduction.Â The result of research showed that (1) lack of paddy (Oryza sativa) production, therefore, is motivated to farmer do the functional change of their farming area becomeÂ  GoldenÂ  Mining area at Jorong Tanjung Pauh IV Nagari District of Sijunjung Regency. In general was caused by not fluent the water stream to make wet their farming and often occur the landslide. (2) The condition of peopleâs income from the golden mining was larger than farming production have motivated people to change the area function from farming area become golden mining area.. (3) The management of golden mining was easier than farming; it motivated the society to do the change of area function at Jorong Tanjung Pauh IV Nagari District of Sijunjung Regency